Biomechanics of L5/S1 in Long Thoracolumbosacral Constructs: A Cadaveric Study. Issue 6 (September 2018) - Lee, Bryan S.; Walsh, Kevin M.; Healy, Andrew T.; Colbrunn, Robb; Butler, Robert S.; Goodwin, Ryan C.; Steinmetz, Michael P.; Mroz, Thomas E.
Study Design: In vitro cadaveric biomechanical study. Objectives: Despite numerous techniques employed to establish solid lumbosacral fixation, there are little biomechanical data correlating fixation methods at L5/S1 to thoracolumbosacral (TLS) construct length. We aimed to determine the optimal construct with the hypothesis that under physiological loads, lumbosacral constructs can be stabilized by L5/S1 anterior lumbar interbody fusion (ALIF) alone, without iliac screw fixation (ISF), and that TLS constructs would require ISF, with or without ALIF. Methods: By using a robot capable of motion in 6 axes, force-moment sensor, motion-tracking camera system and software, we simulated the spinal loading effects in flexion-extension, axial rotation, and lateral bending, and compared torques in different construct groups of T4-S1, T10-S1, and L2-S1. By conducting multidirectional flexibility testing we assessed the effects of constructs of various lengths on the L5/S1 segment. Results: L2-S1 constructs may be equivalently stabilized by L5/S1 ALIF alone without ISF. Longer TLS constructs exerted increasing motion at L5/S1, exhibiting trends in favor of ISF when extending to T10 and statistically improved fixation when extending to T4. Lastly, TLS constructs with ISF exhibited a statistically significant reduction in L5-S1 range of motion from the addition of ALIF when extending to T4-pelvis but not T10-pelvis. Conclusions: We found that ALIF alone may sufficiently support the L2-S1 construct, reducing L5/S1 range of motion and transmitting loads instead to the sacropelvis. Furthermore, ALIF was found to add significant stability to the T4-pelvis construct when added to ISF. This difference was not significant for the T10-pelvis construct.